Маркетинговий напрям в товарно- інноваційній політиці - Сударкіна, Світлана Петрівна; Федченко, В. І. (НТУ "ХПІ", 2014)
Розглядається роль маркетингової складової в товарно-інноваційній політиці підприємства. Встановлення зв’язку складових комплексу маркетингу з етапами створення товару. Аналіз показників конкурентоспроможності. Приведено приклад впровадження інноваційного товару на підприємстві. Побудована матриця «ціна-якість» для систем контролю «Naviland AT-01-UA» підприємства ДНВП «Об’єднання Комунар» та товарів-конкурентів. Оцінка конкурентної позиції даного товару.

The role of the marketing component in inventory innovation policy of the company. Linking components of the marketing mix to the stages of creating the product. The analysis of competitiveness. The example of the introduction of innovative products in the enterprise. Constructed matrix "pricequality" for monitoring «Naviland AT-01-UA» Enterprise SSPE "Kommunar Corporation" and competing products. Assessment of the competitive position of the product. Studies have shown that the production company SSPE "Kommunar Corporation " high quality and average price, and that this segment does not act than a competitor. This ratio "price-quality" provides a competitive product on the market and provides in-depth strategy for market penetration.
Market trend in commodity-innovation policy
Keywords: інноваційна політика; комплекс маркетингу; створення товару; системи контролю; конкурентоспроможність; innovation policy; marketing; product; control system; competitiveness